Learning PowerPoint 97 : introduction (ViaGrafix OklahomaUS, 1999)
Provides a basic introduction to starting and closing PowerPoint viz. the use of menus and toolbars, creating, editing and saving presentations; creating and editing speaker's notes; adding/editing charts; using the slide master; and printing the slide show.
LRC